2022
DOI: 10.3390/math10050694
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Game Analysis of Cooperation and Selfishness in a Random Access Mechanism

Abstract: This paper introduces a general stochastic game analysis of a network scenario consisting of a mix of cooperative and non-cooperative players (i.e., users) under incomplete game information. Users access a shared channel using the Slotted ALOHA mechanism combined with ZigZag Decoding (SAZD). Cooperative players seek to optimize the global utility of the system (e.g., throughput, delay, loss rate) regardless of their individual interests, whereas non-cooperative players act selfishly and optimize their own bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In [13], a two-dimensional Markov chain was used to evaluate the performance of the Slotted ALOHA (SA) and Slotted ALOHA combined with ZigZag Decoding (SA-ZD) protocols in a network with cooperative and selfish users sharing the same wireless channel. The authors found that both protocols performed best with cooperation, but the SA-ZD protocol outperformed SA in all performance metrics.…”
Section: Markov Theory Modelsmentioning
confidence: 99%
“…In [13], a two-dimensional Markov chain was used to evaluate the performance of the Slotted ALOHA (SA) and Slotted ALOHA combined with ZigZag Decoding (SA-ZD) protocols in a network with cooperative and selfish users sharing the same wireless channel. The authors found that both protocols performed best with cooperation, but the SA-ZD protocol outperformed SA in all performance metrics.…”
Section: Markov Theory Modelsmentioning
confidence: 99%
“…In [19], the authors have considered a network scenario consisting of a mix of cooperative and non-cooperative users under incomplete game information. The authors have supposed that the users implement the Slotted ALOHA mechanism combined with ZigZag Decoding to access a shared channel.…”
Section: Related Workmentioning
confidence: 99%
“…If only one source transmit P W wx .T wx Otherwise, (19) where P W wx and T wx are the power consumption and the time duration in the waiting mode, respectively. And E cx can be formulated as:…”
Section: Average Energy Consumptionmentioning
confidence: 99%
“…There are two types of game theory for decision-making: cooperative and non-cooperative games (Mirzaei-Nodoushan et al, 2022). The main distinction between the two is that non-cooperative game theory is chiefly about maximizing participant's interests through the optimization process of their decision and therefore does not have binding agreements between players (Huang & Li, 2022), while cooperative game theory is actually mainly based on agreements for the allocation of participatory benefits (Parrachino et al, 2006) and leads to the best performance (Boujnoui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%